MEDICINAL USES, PHYTOCHEMICAL AND PHARMACOLOGICAL PROPERTIES OF TERMINALIA SAMBESIACA ENGL. AND DIELS (COMBRETACEAE) - MAROYI, ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Terminalia sambesiaca Engl. and Dielsis a small to large tree widely used as traditional medicine in tropical Africa. This study critically reviewed the medicinal uses, phytochemical and pharmacological properties of T. sambesiaca. Literature on medicinal uses, phytochemical and pharmacological properties of T. sambesiaca was collected from multiple internet sources such as Web of Science, Scopus®, SpringerLink®, Google Scholar, SciELO, PubMed®, and ScienceDirect®. Complementary information on medicinal uses, phytochemical, and pharmacological properties of T. sambesiaca was gathered from pre-electronic sources such as book chapters, books, scientific reports, and journal articles obtained from the University library. This study revealed that T. sambesiaca is used as traditional medicine against menstrual problems, infertility in women, stomach ulcers, appendicitis, backache, bilharzia, cancer, cough, diarrhea, earache, infectious diseases, intestinal worms, pneumonia, and syphilis. Phytochemical research identified fatty acids, flavonoids, cardiac glycosides, saponins, triterpenoids, sterols, isochromans, esters, alkylamine, ligands, oxacycle, phenols, polyketides, ceramides, and chromones from the leaves, roots and stem bark of T. sambesiaca. Ethnopharmacological research revealed that the phytochemical compounds isolated from T. sambesiaca and crude extracts of the species showed antibacterial, anti-Neisseria gonorrhoeae, antimycobacterial, antifungal, antioxidant, antiproliferative, and cytotoxicity activities. Since T. sambesiaca extracts are widely used as sources of traditional medicines, there is need for extensive phytochemical, pharmacological, toxicological evaluations, in vivo and clinical studies.